Composition of Solvent-Extractable Organic Matter in Atmospheric Particles and Soils Collected at Scott Base, Antartica. - bin Abas, M. Radzi; Abd. Rahman, Noorsaadah; M.J. Omar, Nasr Yousef; Sulaiman, Nik Meriam; Abu Samah, Azizan; Simoneit, Bernad R.T. (Malaysian Journal of Science, 2009)
Atmospheric particulate matter and soil samples were collected around Scott Base, Antarctica and analyzed for solvent extractable organic compounds. Homologous compounds such as nalkanes, n-alkanols and n-alkanoic acids were present in all samples and are indicative of contamination from anthropogenic activities and to a lesser extent from natural microbial input. Extractable PAH and oxy- PAH also confirm vehicular exhaust as a contributor to the organic particulate matter emitted into the atmosphere at Scott Base. Petroleum molecular markers such as pristane and phytane, as well as hopanes and steranes were also found in some soil and air samples. The concentrations of organic compounds were similar to those reported for rural locales in the northern hemisphere, suggesting that activities at Scott Base are contaminating the environment.